Sentinel Lymph Node Biopsy in High-Risk Cutaneous Squamous Cell Carcinoma: Analysis of a Large Size Retrospective Series. Issue 7 (July 2021) - Tremblay-Abel, Valérie; Poulin, Marc-Antoine; Blouin, Marie-Michèle; Parent, François; Perron, Émilie
Abstract : BACKGROUND: One of the most important prognostic factors for mortality in cutaneous squamous cell carcinoma (cSCC) is the development of nodal metastasis. There is no consensus regarding which patient with cSCC should be offered sentinel lymph node biopsy (SLNB). OBJECTIVE: This study aimed to establish the rate of positive SLNBs among patients with high-risk cSCCs and to identify which high-risk features are associated with a positive SLNB. METHODS: Five-year retrospective case series in an academic tertiary care center reviewing 93 SLNBs. RESULTS: Of the 93 SLNBs performed, 5 (5.4%) were positive. Three patients (3/5) had neck dissection and one (1/5) had radiation therapy, with no recurrence at the time of last follow-up. A tumor diameter ≥2 cm, a tumor depth >6 mm or below subcutaneous fat, perineural invasion of nerves with a diameter ≥0.1 mm, moderate or poor histological differentiation, lymphovascular invasion, and immunosuppression were associated with a positive SLNB. All tumors with a positive SLNB were classified as T2b according to the Brigham and Women's Hospital (BWH) tumor staging. LIMITATIONS: Retrospective study and absence of a control group. CONCLUSION: Sentinel lymph node biopsy can be considered for BWH T2b and T3 tumors. However, more randomized controlled studies are needed.